Pengaruh Kecerdasan Adversitas, Perhatian Orangtua dan Efikasi Diri Terhadap Hasil Belajar Biologi Siswa Kelas XI MIA SMAN Se-Kabupaten Tana Tidung - Arni Arni; Yusminah Hala; Muhiddin Palennari (Universitas Negeri Makassar, 2022)
This study aims to examine the influence of adversity intelligence, parents’ attention, and self-efficacy on Biology learning outcomes. This type of study is an expost facto research with a population of all students of grade XI at SMAN in Tana Tidung district, namely SMAN 1 Tana Tidung, SMAN 2 Tana Tidung, and SMAN TU 1 Tana Tidung. The total population was 129 people and based on the sample calculation using the Slovin’s formula, the sample was obtained with 97 people. The sampling technique emplooyed cluster sampling technique. The research instruments used were questionnaires on adversity intelligence, parents’ attention, and self-efficacy as well as documentation of Biology learning outcomes. The data obtained were then analyzed by using descriptive analysis and inferential statistical analysis. The variables of the consisted of independent variables, namely adversity intelligence, parents’ attention, and self-efficacy; whereas, the dependent variable was learning outcomes. Based on the results of inferential analysis and the research results, it is discovered that adversity intelligence has a direct influence on learning outcomes, the parents’ attention has a direct influence on learning outcomes, the self-efficacy has a direct influence on learning outcomes, the adversity intelligence and parents’ attention have an indirect influence through self-efficacy on learning outcomes.